“Space, Mass, Surface in Architecture”: Conceptualization of Spatial Categories and a Building as a Border in Architectural Thought and Practice of the Soviet Constructivism - Bass, Vadim (Actual Problems of Theory and History of Art, 2020)
In the post-revolutionary years Soviet architects developed new system of professional thought based on the conceptualization of space (and also on the fashion on psychology). This “spatial turn” was common at the beginning of the Modern movement. The very model of the architects’ activity and their selfperception changed dramatically: instead of shaping volumes they started “setting the borders” and “organizing” space with surfaces. New focus in Constructivist architecture was reinforced with ideas of expansion and space exploration (popular since the late 19th century) and the “cosmic” vision of Russian Avant-garde art.The social concern of professional community and the vision of architecture as a field of social interactions contributed to this changing perspective and resulted in new plans and functional arrangement of buildings (e.g. commune houses) as well as new town-planning concepts (linear city, parabolic city). The new grade of flexibility achieved using concrete framework and curtain walls changed the architects’ attitudes towards both internal structure and the surface of building.Soviet architects of the 1920s managed to establish new spatial concept as the pedagogical basis of architectural school, starting from Nikolay Ladovsky’s course “Space” at VKhUTEMAS. This system, converted into textbooks on “Volumetric-Spatial Composition,” survived in the period of Stalinist anti-Modernist reaction. Even today it lies in foundation of Russian architectural school. The article examines the concept, itssources, establishment, and the reasons for its persistence.
Keywords: Soviet architecture; Constructivism; architectural education; architectural propaedeutics; architectural theory; space in architecture